Kualitas Pelayanan Publik Kecamatan setelah Perubahan Kedudukan dan Fungsi Camat sebagai Perangkat Daerah - J., ROZY AFRIAL (UI Scholars Hub, 2011)
This research aims to analyze the quality of subdistrict public services in decentralization era, identify services dimensions or attributes that are prioritized by subdistrict for a better performance, and conduct comparative study to analyze whether a subdistrict with larger delegated authorities has a better quality of public services. The analysis was conducted using the Service Quality (ServQual) that had been developed into Importance Performance Analysis (IPA). The research was conducted through surveys in two locations i.e. Katapang Subdistrict in Bandung and Dramaga Subdistrict in Bogor, on three types of services namely 1) civil administration/registration services 2). Business license services and 3). Building construction license services.The research result showed that although the subdistricts had legally and formally shifted into local government institution, the quality of public service performance is still not optimal. This was indicated by the lower performance index as well as the importance index of the respondents for both subdistricts, in other words there were gaps between respondents perception and respondents expectation on public service quality.